The Influence of Globalization and Technological innovations on Painting with other Artistic Trends in Nigeria - Olaleye, Emmanuel; Kafaru, Abiodun; Kosoko, Kazeem Olojo -; Opadosu, James (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2471, 2026)
This paper explores the current trends and influences in Nigerian painting, by groping how modern-day artists and their artistic practices could adapt to the western artistic styles and practices to build a visual language and connection with the western artists by advancing their artworks, and exploring various types of contemporary paintings that emerged in the last decade of this 21 st century. Thus, it is evident that contemporary Nigeria paintings have a rich historical background that is still significantly shaping the modern expressions of Nigeria painters in terms of instinct, cognition, and creativity in their artistic practices. Moreover, this paper critically ― analyzed the key role of how these trends has brought and increased an international exposure for Nigerian artists (painters) and their artworks (paintings) through colonial influence and democratization of art distribution through technology (artificial intelligence) and digital platforms such as international exhibitions, virtual exhibitions, publications, and social media networks. Based on the articulation of this paper, it concludes that Nigerian painters can navigate and intersect their artistic tradition with modern practices — in order to stand the grounds of contributing, competing, and being approved in the stage of global art discourse. Keywords: Contemporary Nigerian Art, Painting, Globalization, Technology, Identity, Modernism.